Justice for Muslim Women in India: the sinuous path of the All India Muslim Women Personal Law Board1 - Dequen, Jean-Philippe (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
Muslim Women movements in India have been very active in the past decade, attracting attention both in the Sub-Continent and beyond. This article vows to present a particular trend of this activism centred on the legal sphere, moreover within the frame of the Muslim personal law system and its non-State adjudicative bodies. Through the All India Muslim Women Personal Law Board (AIMWPLB), it will present the example of an attempt to challenge the ‘patriarchal’ legal discourse on Islamic Law by procuring an alternative dispute resolution forum specifically aimed at Muslim women’s issues, as well as advocating for a more gender equal interpretation of the Quran through the prism of ‘Islamic Feminism’. However, it will show that despite its President’s tremendous efforts, the AIMWPLB’s scope remains limited. Although establishing a somewhat successful mediation centre in the Lucknow area, it has for the moment failed to extend its reach in the rest of the Indian Territory. Likewise, its particular discourse on Islamic Law has had but little influence on its overall application in India, and paradoxically could even be counter-productive towards its progression towards a gender equalitarian interpretation.